The Effects of Sharia Financial Literacy and Korean Pop Culture on K-Pop Merchandise Purchase Decisions - Kesuma, Suci Andini; Marliyah, Marliyah; Aisyah, Siti (Universitas Trunojoyo Madura, 2025)
The expansion of the South Korean entertainment sector, particularly the K-Pop phenomenon, has had a tremendous influence on several nations, including Indonesia. In 2023, K-Pop goods sales increased by 74% compared to the previous year. This K-Pop cultural practice encourages fans to spend money on products from idol groups they adore, often without thinking about the long-term financial implications.This research seeks to investigate the impact of sharia financial literacy and K-Pop culture on K-Pop product purchase decisions among fans in Indonesia, specifically among the K-Popers community in Medan. This study employs a quantitative approach with a survey technique to determine the association between independent factors (sharia financial literacy and K-Pop culture) and the dependent variable (buy decisions of K-Pop items), with a sample size of 96 respondents.The study indicates that sharia financial literacy positively impacts purchasing decisions (t = 7.543, p 0.005). This is consistent with prior study, which found that financial literacy plays a major influence in purchasing decisions, particularly in the setting of Sharia, which emphasises prudent financial management in accordance with Islamic principles. The t-test study demonstrates that K-Pop culture has a positive and substantial impact on purchase decisions (t = 3.616, p 0.005), consistent with earlier studies suggesting that culture influences an individual's preferences and purchasing choices.